Different Clinicoradiological Characteristics of Posterior Reversible Encephalopathy Syndrome in Pediatric Oncology and Post-Bone Marrow Transplantation Cases: A Retrospective Study - Shash, Hwazen; Aldaama, Saad; Omer, Hala; Alafghani, Sameera (Frontiers in Neurology, 2022)
Posterior reversible encephalopathy syndrome (PRES) is receiving increasing recognition in pediatrics. However, comparisons between PRES in pediatric oncology and post-bone marrow transplantation (BMT) are lacking. Therefore, we aimed to describe the risk factors and clinical and radiological features of PRES and investigate the differences between PRES in pediatric oncology and post-BMT. The PRES data of 13 patients from our center were combined with those of 217 cases from the PubMed, Scopus, and Web of Science databases. The patients were divided into either an oncology or a post-BMT group. We included 230 patients in the analysis, 26.1% of whom belonged to the post-BMT group. Oncology patients developed PRES at a younger age (p = 0.010) and were more likely to develop encephalopathy (p = 0.004). Systemic hypertension (S-HTN) preceding PRES occurred in 43.5% (66/154) of patients. Post-BMT patients were more likely to have S-HTN (p = 0.003). Cyclosporine levels were detected in 37 patients; 40.5% had supra-therapeutic levels. The radiological findings were atypical in 74.3% of patients, and delayed repeated imaging increased the occurrence of resolution (p = 0.004). Sixteen (7%) patients developed PRES recurrence after a median of 8 weeks, with the between-group difference being non-significant. Oncology patients were more likely to develop chronic epilepsy, while BMT patients were more likely to develop rare neurologic abnormalities (p < 0.001). In conclusion, atypical clinical presentation and imaging findings should not hinder the diagnosis of PRES. S-HTN is a risk factor, particularly in post-BMT patients. Supra-therapeutic levels of cyclosporine and previous exposure to immunosuppression did not increase the risk of recurrence.